2005
DOI: 10.1111/j.1442-2050.2005.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical exercise on esophageal motility in patients with esophageal disease

Abstract: The most common type of esophageal dysfunction associated with chest pain is gastroesophageal reflux, which may be induced by exercise. The effect of exercise on esophageal function has mainly been investigated in normal subjects or trained athletes. Few studies have investigated exercise and esophageal motility disorders. One hundred and thirty-five patients underwent ambulatory esophageal manometry and pH monitoring, before, during and immediately after moderate exercise. Patients were divided into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The consistency of pace during walking may also be important. Ravi et al 20 found treadmill based walking at 1 km/h and 4.2 km/h associated with reflux events, although no analysis of BGT versus exercise time was undertaken, making comparisons with the current study limited. Despite this limitation, the need to maintain a continual speed on a treadmill, even at a slow rate, may have contributed to the raised frequency of reflux events.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…The consistency of pace during walking may also be important. Ravi et al 20 found treadmill based walking at 1 km/h and 4.2 km/h associated with reflux events, although no analysis of BGT versus exercise time was undertaken, making comparisons with the current study limited. Despite this limitation, the need to maintain a continual speed on a treadmill, even at a slow rate, may have contributed to the raised frequency of reflux events.…”
Section: Discussionmentioning
confidence: 86%
“…Despite this limitation, the need to maintain a continual speed on a treadmill, even at a slow rate, may have contributed to the raised frequency of reflux events. 20 In contrast, participants in the current study were permitted to vary the pace during the 6MWT, according to their physical limitations. While the intensity of the 6MWT was likely to be limited by respiratory symptoms in some patients, the instructions for the test included directions to "cover as much distance as possible in 6 minutes."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations